Research on Environmental Sustainability of Coal Cities: A Case Study of Yulin, China - Xiaowei Zhai; Zhuo Cheng; Keyu Ai; Bo Shang (Energies, 2020)
Coal cities are an essential impetus for economic development and urbanization processes in China. However, a series of environmental issues provoked by resource exploitation cause the environmental sustainability of coal cities to face enormous challenges. Therefore, on the basis of the time series data of Yulin City from 1996 to 2017, this paper explores the nexus between socioeconomic development and industrial “three wastes” emissions by adopting the Tapio decoupling model, the environmental Kuznets curve (EKC) hypothesis, and the vector auto-regressive (VAR) model. The results show that Yulin’s economic development remains in an extensive stage and will not decouple from the environmental pollution in a short time. Except for the nexus of industrial solid waste and economic growth, which is an inverted U-shaped, the EKC hypothesis is not valid for industrial wastewater and industrial waste gas. Through the VAR (2) model, the impact of per capita gross domestic product (GDP) on industrial waste emissions is consistent with the results of the EKC hypothesis. Moreover, industrial waste emissions have a positive correlation with the per capita raw coal output, the energy consumption per unit of GDP, and the proportion of secondary industry. Hence, it is necessary to formulate targeted measures from industrial restructuring, industrial chain extension, governance model optimization, and waste comprehensive utilization to realize the environmental sustainability of coal cities.